Seasonal Pattern in the Diagnosis of Gestational Diabetes Mellitus in Southern Sweden - Anastasia Katsarou; Rickard Claesson; Claes Ignell; Nael Shaat; Kerstin Berntorp (Journal of Diabetes Research)
Aim. The aim of this study was to examine seasonal patterns in glucose tolerance and in the diagnosis of gestational diabetes mellitus (GDM). Methods. Altogether, 11 538 women underwent a 75-g oral glucose tolerance test (OGTT) in the twenty-eighth week of pregnancy during the years 2003–2005 in southern Sweden. GDM was defined by the 2-h capillary glucose concentration in the OGTT (≥8.9 mmol/L). Chi-squared test, analysis of variance, and regression analyses were used for statistical evaluations. Results. The seasonal frequency of GDM ranged from 3.3% in spring to 5.5% in summer (p<0.0001). Mean 2-h glucose concentrations followed the same seasonal trend, with a difference of 0.15 mmol/L between winter and summer (p<0.0001). The 2-h glucose level increased by 0.009 mmol/L for every degree increase in temperature (p<0.0001). In regression analysis, summer (June–August) was associated with increased 2-h glucose level (p<0.001) and increased frequency of GDM compared to the other seasons (odds ratio 1.51, 95% confidence interval 1.24–1.83, and p<0.001). Conclusions. Our findings suggest seasonal variation in the 2-h glucose concentration in the OGTT and in the proportion of women diagnosed with GDM, with a peak in the summer.